Lombard Effect in Polish Speech and its Comparison in English Speech - KLECZKOWSKI, Piotr; ŻAK, Agnieszka; KRÓL-NOWAK, Aleksandra (Archives of Acoustics, 2017)
The first extensive investigation on the Lombard effect with Polish speech has been performed. Characteristic parameters of Lombard speech were measured: intensity, fundamental frequency, spectral tilt, duration of words, duration of pauses and duration of vowels. The effect was investigated in a task involving real communication – solving a Sudoku puzzle. The speakers produced speech in quiet and in three different backgrounds: competing speech, speech-shaped noise and speech-modulated noise. The experimental conditions were held as close as possible to those in the study by Cooke and Lu (2010) so that conclusions could be drawn whether differences between the Lombard effect in Polish speech and English speech existed. Most of the findings on the Lombard effect known from the literature have been confirmed with Polish speech. In three parameters, Polish speakers were more sensitive to modulated backgrounds while English speakers were more sensitive to a stationary background. In both languages, the modulated backgrounds induced speakers to extend pauses in the communication tasks.